The social aspects of child nutrition in Turkey - Cura, Sabiha (The Turkish Journal of Pediatrics, 1961)
A survey of child nutrition in Turkey indicates that a large majority of infants are improperly fed either owing to being kept solely on the breast for too long or to being given supplementary feeding that is poor in protein and rich only in carbohydrates. The situation with regard to older children parallels that of adults, the quality of nutrition depends upon the availability of foods and the income and educational level of the family. It is stated that malnutrition is one of the leading causes of mortality among children and that it is the most important and the most widespread problem encountered by the pediatrician in Turkey.